DETERMINAN AGRESIVITAS PAJAK PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DIBURSA EFEK INDONESIA - Litdia, Litdia; Dyarini, Dyarini; Estiningsih, Wening (Taksasila Edukasi Insani, 2023)
One phenomenon related to tax avoidance is a company in Indonesia, namely PT Bentoel International Investama (Kontan. Co.id. Jakarta, 8/5/2019). This research aims to determine and test the influence of Current Ratio, Market Capitalization and Price Earning Ratio on Tax Aggressiveness in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2018-2021 period. This research uses secondary data, the sampling technique used is Purposive Sampling with a total of 16 companies determined as samples. By using tools, namely SPSS 23 program. Based on research that has been conducted, it shows that partially the Current Ratio and Market Capitalization have no effect on Tax Aggressiveness, while the Price Earning Ratio has an effect on Tax Aggressiveness